The petrology and petrogenesis of the North Motzfeldt Centre, Gardar Province, South Greenland - Finch, A. A.; Goodenough, K M; Salmon, H M; Andersen, T (Mineralogical Magazine, 2001)
North Motzfeldt is an intrusive igneous centre within the Igaliku (formerly spelt Igaliko) complex, Gardar Province, South Greenland. A detailed field description of the centre is given, with preliminary geochemical and isotopic data. The North Motzfeldt centre is intruded into Ketilidian granitoid basement rocks, and current exposure retains parts of the original roof against earlier Gardar eruptives and elastic sediments of the Eriksfjord formation. The unconformity between the Ketilidian and the overlying Eriksfjord is believed to have been crucial in the siting of the centre. The centre is subdivided into two major units, NM1 and NM2. This was followed by significant peralkaline nepheline microsyenite in sheets, characterized by rare element-rich accessory minerals including rinkite-mosandrite, pyrochlore and lavenite. A significant microsyenite body is called NM3. A preliminary Rb-Sr isochron of 1226 +/- 27 Ma indicates a far younger age for the centre than previously thought (similar to 1350 Ma). Cross-cutting relationships between North Motzfeldt and rocks of the adjacent Motzfeldt centre require a reappraisal of the chronology of Motzfeldt magmatism. We suggest that rocks previously believed to comprise the Motzfeldt centre represent the products of multiple phases of magmatism from Early- to Mid-Gardar times.